Business Education vs. Entrepreneurial Attitude of Students of the Faculty of Administrative Sciences of the Universidad Técnica de Ambato - Palacio Fierro, Andrés; Ruth Zamora-Sánchez (My University, 2024)
This research details the entrepreneurial attitude of university students. The study aims to identify the factors influencing the entrepreneurial attitude of students in the Faculty of Administrative Sciences, as well as the importance of business education programs in fostering creativity, critical thinking, and entrepreneurship from early stages of academic training. To achieve this, the research explores students’ intention and motivation towards innovation, risk-taking, and entrepreneurial initiative. The study population consisted of students majoring in Business Administration and Marketing. Dimensions related to risk perception, creativity, motivation, and entrepreneurial intention were assessed. Findings indicate a notable predisposition towards entrepreneurship among university students, highlighting a high propensity for taking calculated risks and a proactive mindset towards problem-solving. Similarly, the influence of educational components was identified. These findings lead to the conclusion that there are significant implications for designing curricula and educational policies aimed at cultivating an entrepreneurial culture in the university environment, thereby promoting the intention to undertake entrepreneurial ventures, enhancing students’ ability to face challenges in the business world, and fostering innovation in the future.
Keywords: Accounting; Entrepreneurial attitude; Knowledge; Perception; Skills